O uso de honeydew por aves (Hemiptera: Coccoidea) na Mata Atlântica do sudeste do Brasil - Capelão, Raissa Sequini (2018)
Honeydew is a carbohydrate solution produced and secreted by scale insects (Hemiptera), which feed on the phloem of host plants, removing nitrogen compounds for protein synthesis. Here we analyzed factors that may affect scale insects (Stigmacoccus paranaenses) (Stigmaccocidae) secretion of honeydew on Inga trees, and described its use as a feeding resource by birds in a rain Atlantic forest area, in southeastern Brazil. We performed 359 hours of observation on 25 focal trees from the first fortnight September 2016 to fortnight September 2017. We recorded twenty-five bird species feeding on honeydew, totaling 3,261 visits. Sixteen of these species were never recorded feeding on honeydew before. Most of the visits occurred in the morning (7:00 am to 8:00 am) and in the winter months, and the most recorded species were Bananaquit (Coerebinae) and Tanagers (Thraupidae). Golden-chevroned Tanager (Thraupidae) was the species that most actively defended the resource, with 44% of all 759 observed agonistic interactions. We verified a seasonal variation in honeydew production, peaking in the austral winter time and absent in the summer. Honeydew consumption is intrinsically linked to variation in its availability, which is negatively affected by temperature. We found evidence of resource partitioning among honeydew consumers, which includes not only birds but several arthropods. Although honeydew may be a seasonal opportunistic resource, it seems to be highly worth defending, because of its high sugar concentration, composition, and its easy-access, leading to a positive trade-off.